Business skills all-in-one for dummies. - Tracy, John A.; Anderson, Mary Ann (Industrial engineer); Anderson, Edward (Edward George); Parker, Geoffrey (Geoffrey G.); Jones, Dawna; Portny, Stanley E. (Stanley Erwin); Elad, Joel; Canavor, Natalie, 1942-; Deiss, Ryan; Henneberry, Russ (--For dummies., 2018)
There are some things that will never go out of style, and good business skills are one of them. With the help of this informative book, youll learn how to wear multiple hats in the workplace no matter what comes your waywithout ever breaking a sweat.Compiled from eight of the best Dummies books on business skills topics, Business Skills All-in-One For Dummies offers everything you need to hone your abilities and translate them into a bigger paycheck. Whether youre tasked with marketing or accounting responsibilitiesor anything in betweenthis all-encompassing reference makes it easier than ever to tackle your job with confidence.